2015
DOI: 10.5152/balkanmedj.2015.15302
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Metallo Beta Lactamases and Oxacilinases in Carbapenem Resistant Acinetobacter baumannii Strains Isolated from Inpatients

Abstract: Acinetobacter baumannii strains are non-fermenting aerobic Gram-negative bacteria that play an important role in hospital infections. Difficulties in the treatment and control of this growing threat make this pathogen an important health problem (1).Resistance to beta-lactam antibiotics is widespread among Acinetobacter strains. Plasmid-mediated metallo beta-lactamases Background: Resistance to beta-lactam antibiotics is widespread among Acinetobacter strains. Plasmid-mediated metallo beta lactamases (MBL) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 25 publications
6
21
0
1
Order By: Relevance
“…2). Such prevalence is in line with the findings of other studies [9,10]. However, compared to others, the sample size in our study was relatively small; therefore, the study should be expanded to obtain more statistically significant data.…”
Section: Prevalence Of the Four Targeted Resistance-associated Genessupporting
confidence: 92%
See 1 more Smart Citation
“…2). Such prevalence is in line with the findings of other studies [9,10]. However, compared to others, the sample size in our study was relatively small; therefore, the study should be expanded to obtain more statistically significant data.…”
Section: Prevalence Of the Four Targeted Resistance-associated Genessupporting
confidence: 92%
“…The results of the antibiotic sensitivity test of eight β-lactam antibiotics, as indicated in 19/58 samples, revealed that three antibiotics, CRO, FEP (a cephalosporin), and Screening of the 58 samples (52 DNA and established multiplex PCR showed that the presen e (47/58, 81%), following by OXA-23: (63.8%, 37/58) (1.7%), the lowest, was found in only one sample (Fig with the ndings of other studies [9,10]. However, c size in our study was relatively small; therefore, the obtain more statistically signi cant data.…”
Section: Correlation Between Genomic Profiling and Antibiotic Susceptsupporting
confidence: 58%
“…Several sudden outbreaks of the bacteria are reported annually from hospitals around the world, indicating the importance of the bacteria and the need for a suitable plan to prevent infection, particularly by resistant strains. Many studies conducted in hospitals during the sudden outbreaks, revealed that hospital environments had been the source of infection in most cases (19). Various studies showed that Acinetobacter could survive for 16 weeks on dry surfaces of an environment; and this is considered as an alarm for its treatment because the isolates of A. baumannii could be isolated repeatedly from all various surfaces, indicating its high adaptability to incompatible environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…K€ uç€ ukbasmaci et al [30] did not detect any MBL resistance gene by multiplex PCR in any one of the 51 isolates of P. aeruginosa. Aksoy et al [31] did not detect any MBL gene in 52 IMP resistant A. baumannii isolates but reported OXA-23-like and OXA-51-like resistance genes. In a study from northern Turkey, among 100 P. aeruginosa isolates studied by Ozgumus et al [32], VIM-type MBL was detected in one strain, IMP-1 type MBL was detected in nine strains, and clonal analysis of the IMP-1 type positive isolates revealed that all the strains were clonally related.…”
Section: Comparison Of Rt-pcr With Phenotypic Methods For Metallo-betmentioning
confidence: 96%